Targeted localization of Inn1, Cyk3 and Chs2 by the mitotic-exit network regulates cytokinesis in budding yeast - Meitinger, Franz; Pereira, Gislene (Journal of cell science, 2010)
The mitotic-exit network (MEN) is a signaling pathway that is essential for the coordination of mitotic exit and cytokinesis. Whereas the role of the MEN in mitotic exit is well established, the molecular mechanisms by which MEN components regulate cytokinesis remain poorly understood. Here, we show that the MEN controls components involved in septum formation, including Inn1, Cyk3 and Chs2. MEN-deficient mutants, forced to exit mitosis as a result of Cdk1 inactivation, show defects in targeting Cyk3 and Inn1 to the bud-neck region. In addition, we found that the chitin synthase Chs2 did not efficiently localize at the bud neck in the absence of MEN activity. Ultrastructural analysis of the bud neck revealed that low MEN activity led to unilateral, uncoordinated extension of the primary and secondary septa. This defect was partially suppressed by increased levels of Cyk3. We therefore propose that the MEN directly controls cytokinesis via targeting of Inn1, Cyk3 and Chs2 to the bud neck.